PENINGKATAN KETERAMPILAN PEMUDA MELALUI PELATIHAN OTOMOTIF BERBASIS PEMBERDAYAAN DI KAMPUNG HULURAWA, DESA BANTARSARI - Yusup Arya pudholi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
This study aims to analyze the implementation of empowerment-based automotive training and its effect on improving youth skills in Kampung Hulurawa, Bantarsari Village. This research employed a qualitative approach with a case study design. Data were collected through observation, interviews, and documentation involving 24 training participants, with 21 participants, 2 instructors, and 1 village head serving as the main informants. The training was organized by the Youth Organization and the Bantarsari Village Government for three days and covered spare part identification, oil changing, carburetor servicing, tune-up, and basic electrical systems. The findings revealed that participants’ understanding of basic automotive skills increased from 20% before the training to 80% of participants being able to perform light motorcycle servicing after the training. The program also produced tangible impacts, with 7 participants obtaining internship opportunities at local workshops and 5 participants establishing a home-based motorcycle service business collectively. The success of the program was supported by village government support, experienced instructors, and adequate training equipment, while the main obstacles included participant tardiness and limited spare parts. It can be concluded that empowerment-based automotive training is effective in improving youth skills, self-confidence, and economic independence. These findings imply that similar programs can serve as a model for youth empowerment in rural areas